A novel scatterer model for the security of key generation based on DISC model. Issue 1 (April 2021) - Yang, Yuanhang; Zeng, Xin; Xue, Xiaoping
Abstract: Physical layer security is a method of extracting encryption keys according to the randomness of reciprocal propagation channels between legitimate users, and the security under normal circumstances is ensured according to the decorrelation between these channels and those tapped by eavesdropper. However, evidences show that in some scenarios, such as the environment of quasi-static or insufficient scattering, the tapped channel still has a strong correlation with the legitimate channel, leading to bits leakage and security imperilment of key generation. The effect of introducing scatterers has been experimentally proved, however, these studies are based on fixed positions or special models and there is yet a lack of research on the influences brought by various scatterer distributions. In this paper, we introduce scatterers into single-bounced DISC model and control their distributions through a probability density function with two degrees of freedom, aiming to deeply investigate the impacts of scatterer distribution on channel decorrelation as well as key security. Simulation results prove that spiral correlation between tapped channel and legitimate channel can be effectively reduced by increasing scatterers and arranging them around the legitimate receiver, which make contributions to reduce key leakage and improve security.